Identifying spatial movements and residency of pelagic thresher sharks (Alopias pelagicus) using satellite and passive acoustic telemetry to inform local conservation in central Indonesia - Shidqi, Rafid A.; Erdmann, Mark V.; Setyawan, Edy; Lezama-Ochoa, Nerea; Sari, Dewi R.; Sianipar, Abraham B.; Stewart, Joshua D.; Croll, Donald A. (Frontiers in Fish Science, 2024)
The pelagic thresher shark (Alopias pelagicus) is globally endangered, threatened by bycatch, and targeted in industrial and artisanal fisheries in Indonesia. However, a lack of information about their ecology, particularly movement and habitat use, hinders the development of science-based conservation measures to protect the species. Here, we report our research, which is the first to use a combination of satellite and passive acoustic telemetry to investigate the movement and residency of the pelagic thresher shark within Indonesia's waters, especially in areas impacted by local fisheries. A total of 24 sharks were tagged with archival satellite tags (n = 9), internal acoustic tags (n = 10), and both tags (n = 5) in Selat Pantar Marine Protected Area (MPA). The tagged sharks, dominated by